Phantom busters. 3 - Shoco (Shonen Jump manga., 2026)
Why bother fighting spectral foes like all the other exorcists when you can just eat them? Straight A student Eugene Korekishi doesn't believe in ghosts...but his classmate Mogari Shishikuno is an exorcist who swallows them whole! Mogari can't see ghosts on his own, but once he and Eugene meet someone with the sight, there's only one path left--form an exorcist club at school and embark on anything but a normal high school life! From karaoke battles with ghosts to run-ins with the student council, there's never a dull day in the lives of the Phantom Busters! But when they discover that Kanzaki is struggling with a certain hangup concerning his psychic abilities, the crew decides to hold a sleepover to help him open up to them!